1992
DOI: 10.1042/bj2860141
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of deuterium from [1,1-2H2]ethanol to steroids and organic acids in the rat testis

Abstract: Rats were given [1,1-2H2]ethanol in a single dose, and the 2H content was determined in testicular steroids and in organic acids of low molecular mass in the testis, liver and blood. The acids were quantified by capillary gas chromatography/mass spectrometry of t-butyldimethylsilyl derivatives with [2H4]lactate as internal standard. In addition to lactate, pyruvate, 3-hydroxybutyrate and acids of the tricarboxylic acid cycle, the testis was shown to contain 2-hydroxybutyrate, 2-hydroxy-2-methylbutyrate, 2-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The results showed that ethanol increased the ratios between 3β-hydroxy-∆ 5 -/3oxo-∆ 4 -steroid couples, compatible with an inhibition of testosterone biosynthesis. Later studies with [1,1-2 H 2 ]ethanol indicated that this was a direct effect of testicular ethanol metabolism on the redox state, not mediated by lactic acid from the liver (98). Thus, it appears that ethanol-induced redox changes can be of endocrinological importance both via effects on the metabolism and the biosynthesis of steroid hormones.…”
Section: Alcohol and The Metabolism And Biosynthesis Of Steroids And mentioning
confidence: 99%
“…The results showed that ethanol increased the ratios between 3β-hydroxy-∆ 5 -/3oxo-∆ 4 -steroid couples, compatible with an inhibition of testosterone biosynthesis. Later studies with [1,1-2 H 2 ]ethanol indicated that this was a direct effect of testicular ethanol metabolism on the redox state, not mediated by lactic acid from the liver (98). Thus, it appears that ethanol-induced redox changes can be of endocrinological importance both via effects on the metabolism and the biosynthesis of steroid hormones.…”
Section: Alcohol and The Metabolism And Biosynthesis Of Steroids And mentioning
confidence: 99%
“…Martel et al concluded that the "widespread distribution of 17␤-HSD in rat clearly indicates the importance of this enzyme in peripheral sex steroid formation." Norsteen-Hoog et al (1992) investigated the transfer of deuterium from 1,1-dideuteroethanol to steroids in isolated rat testis; no deuterium was found in pregnenolone or testosterone. The transfer of deuterium from 1,1-dideuteroethanol to testosterone requires a change in the redox state of the oxidized nicotinamide adenine dinucleotide phosphate system, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%